NCL-7, a novel all silica analog of polymorph B rich member of BEA family: synthesis and characterization - Kadgaonkar, Mahesh D.; Kasture, Mahesh W.; Bhange, Deu S.; Joshi, Praphulla N.; Ramaswamy, Veda; Kumar, Rajiv (Microporous and Mesoporous Materials, 2007)
{Polymorph B-rich BEA type structure, NCL-7, was synthesized using hydrothermal method in fluoride medium using perchloric acid as promoter. The samples were characterized using XRD, low temperature N-2-adsorption and Si-29 MASNMR. As the structure of beta is highly disordered Rietveld refinement of powder XRD patterns is precluded. Phase composition is derived using the simulated patterns for the random intergrowths of polymorph A and B by DIFFaX. The stacking direction c' is perpendicular to the a'b' plane of the layer. The composition of polymorph B is found to be ca. 60-65%. Two other structures namely NCL-5 and NCL-6 with varying degree of polymorph B enrichment were also synthesized. Synthesis parameters such as effect of H2O/SiO2, TEAOH/SiO2, HClO4/SiO2 and crystallization temperature were studied thoroughly. The present article explains for the first time the synthesis and characterization of NCL-7, an analog of BEA type family with enrichment of polymorph B and its comparison with normal beta (*
Keywords: B-polymorph; DIFFaX; Promoter; Reitveld refinement; synthesis; zeolite beta